Preparation and thermal storage performance of phase change ceramsite sand and thermal storage light-weight concrete. (September 2021) - Li, Min; Zhou, Dongyi; Jiang, Yaqing
Abstract: 1. Abstract: In this study, preparation and thermal storage performance of phase change ceramsite sand and thermal of storage light-weight concrete are studied. Sintering-free ceramsite and ceramsite sand with high adsorption ability were prepared. Then, paraffin is incorporated into them to fabricate phase -change coarse aggregate and phase-change fine aggregate, respectively, which are used to prepare thermal storage light weight concrete. Brunauer-Emmett-Teller (BET), Mercury intrusion method (MIP) Differential Scanning Calorimetry (DSC), Fourier Transform Infrared (FT-IR) and X-ray diffraction (XRD) are employed to analyze the specific surface area, pore structure, thermal properties, chemical composition and phase composition of phase change aggregate. The compressive strength and the temperature regulation performance of the thermal storage light weight concrete are studied. The results show that the porosity of the ceramsite sand is 58.27% when the content of expanded perlite and Aluminum is 30 g and 1 g, respectively. In addition, the adsorption rate of paraffin in the ceramsite sand is 42.75 wt% and the melting latent heat of the phase change ceramsite sand is 45.64 J/g. The compressive strength of the prepared thermal storage light-weight concrete meets the strength level of lightweight concrete 15 Mpa (LC15) Moreover, the prepared concrete shows light-weight character and good temperature regulation performance. The prepared thermal storage concrete shows a good application prospect in energy-saving and the use of renewable energy. Highlights: Expanded perlite and Al powder are used to prepare sintering-free ceramsite/ceramsite sand. With high adsorption ability. Coating ceramsite/ceramsite sand with cement could prevent leakage and improve the interface in concrete. The PCM concrete100F50C could decrease the peak temperature by 3 °C. The light shows light-weight character and good temperature regulation performance.